Difference in the intraday return-volume relationships of spots and futures: A quantile regression approach - Jaeram Lee; Geul Lee; Doojin Ryu (Kiel Institute for the World Economy (IfW), 2018)
This study examines the difference in the intraday return-volume relationships of spot and index futures. Quantile regression analyses show that the widening effect of the stock trading volume on the distribution of spot returns disappears within a short period of time, whereas that of the futures trading volume remains over the long term. The short-term effect of the stock volume and the long-term effect of the futures volume are both consistent for contemporaneous trading volumes. Furthermore, the futures volume has a significantly positive effect on the option-implied volatility, whereas the stock volume is only associated with the implied volatility of at-the-money options, which can be traded quickly. In contrast, the implied volatility of out-of-the-money options, which are highly speculative, is strongly related to the futures volume. The findings suggest that the stock volume is mainly induced by hedging demand or disagreements of opinion, whereas the futures volume contains information about price movements.
Keywords: C22; G12; G14; 330; information channel; intraday information content; KOSPI 200 futures; option-implied volatility; return-volume relationship; quantile regression